Usual and unusual CIELAB color parameters for the study of peat organic matter properties: Tremoal do Pedrido bog (NW Spain). (April 2015) - Sanmartín, P; Silva-Sánchez, N; Martínez-Cortizas, A; Prieto, B
Abstract: We have tested the practical application of color measurements in the study of organic matter properties (C and N content, C/N ratios, degree of peat humification-DPH) of a 335 cm long peat core sampled at Tremoal do Pedrido bog. Usual and unusual CIELAB color parameters were measured on samples that were sectioned at high resolution (slices of 1 cm in thickness). The objective of the study is twofold: ( i ) describe a rapid, cost-effective and non-destructive method of assessing peat properties without the need of extractions and chemical methods and ( ii ) contribute to further research on applied colorimetry using the well-known CIELAB coordinates: L*, a*, b*, C*ab and hab ('usual CIELAB color parameters') and the less well-known CIELAB parameters: [a* x b*], [a*/b*], [(a*/b*) x 1000], [1000 x a*/(L*+ b*)], [2000 x a*/(L* x b*)] and RLab = [a*(a* 2 +b* 2 ) 1/2 10 10 ]/(b* x L* 6 ) ('unusual CIELAB color parameters'). Our findings show that L* and hab coordinates as well as [(a*/b*) x 1000], [2000 x a*/(L* x b*)] and RLab parameters give the best bivariate Spearman's correlations. Linear regression equations were calculated to predict peat properties from all CIELAB parameters under study and a notable fit (R 2 : 0.65-0.79) was obtained. The evaluation presented here indicates that the determination of usual and unusual CIELAB parameters offers potential for the study of peat organic matter properties and encourages the routine application of this methodology on other peat cores and organic soils.